Mathematical Modeling of Red Blood Cell Shape Change in Early Neuroprotection With Moderate Therapeutic Effect of Hypothermia - Morozova , Oksana; Batyuk , Liliya; Muraveinik , Oksana (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3):290